Volatilidade de capitais externos no Brasil: uma questão de relações políticas internacionais - Cassano, Francisco Américo (2006)
This study aims to understand the effects that Brazilian external politics exerts on foreign capital flow into the country in the respective periods of government, starting in1947. The subject is justified by the existence of a large volume of resources available in the international financial market and by the rapid adaptation of the poorer countries to the regulations defined by the investors. A theoretical reference was made to allow the hypothesis confirmation that an aligned external politics with the developed countries is fundamental to an increase of the foreign direct investments in Brazil. To verify scientifically this hypothesis, a search in two parts was done: a survey of documents about the Brazilian external politics definition with the respective content analysis, and, a quantitative analysis for the confirmation of qualitative analysis. The results obtained allowed to confirm the hypothesis that the alignment with developed countries, with the increase of direct investments, was be fundamental for Brazil s development in the studied period. Besides, it was possible to conclude that such investments interfere in the national PIB, according the constructo defined in the study. These conclusions allow suggesting to the Brazilian external policy makers not to despise the alignment with developed countries, for a most favorable capitation of external resources